Clinical pharmacokinetics of potassium competitive acid blockers: a systematic review and meta-analysis - Liu, Jiaqi; Hahn, Jongsung (Frontiers in Pharmacology, 2025)
BackgroundPotassium competitive acid blockers (P-CABs) are a new class of acid suppressants that provide rapid and sustained inhibition of gastric acid secretion. Understanding the pharmacokinetic (PK) characteristics of P-CABs in various therapeutic uses is essential for optimizing treatment. This study aims to investigate the PK properties of P-CABs, focusing on drug interactions, food effects, and formulation impacts on their exposure and bioavailability.MethodsWe systematically searched MEDLINE and Embase up to July 2024. The search terms included “Potassium competitive acid blockers” or “P-CABs” or “revaprazan” or “vonoprazan” or “tegoprazan” or “fexuprazan” or “keverprazan” or “zastaprazan” and “pharmacokinetics”.ResultsA total of 37 studies were included. Meta-analysis and qualitative studies indicated that clarithromycin significantly increased vonoprazan and tegoprazan exposure [geometric mean ratio (GMR) (90% confidence interval (CI))] of AUC and Cmax: 1.565 (1.443, 1.687) and 1.538 (1.454, 1.621) for vonoprazan, 2.624 (2.513, 2.735) and 1.876 (1.771, 1.981) for tegoprazan, respectively. Vonoprazan had more of an inhibitory effect on cytochrome P450 (CYP) 3A and CYP2C19 compared to tegoprazan. P-CABs showed minimal interactions with nonsteroidal anti-inflammatory drugs or aspirin and were largely unaffected by food intake, except keverprazan and zastaprazan, which showed increased exposure.DiscussionIt is important to select the appropriate P-CABs by considering the degree of influence on CYP enzymes, the dosage form, and food interactions. Studies on the interaction between P-CABs and antibiotics used to treat H. pylori infections, such as metronidazole, tetracycline, levofloxacin, or rifabutin, as well as non-vitamin K antagonist oral anticoagulants are lacking, and further research is needed.